Evaluation of Myocardial Function in Cases of Gestational Hypertension Using Myocardial Performance Index - Al-Rikabi, Zainab A.; Saeed, Ghassan T.; Haji, Ghazi Farhan (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Gestational hypertension represents a transient period of elevated blood pressure with  special effects on the maternal left ventricle that is different from the effects observed in chronic essential   hypertension; it affects a previously normal heart and lasts for a maximum of nine months associated with   volume and pressure overload on the maternal heart. Tei index (also called myocardial performance index)   was found to be a dependent combined index evaluating the systolic and diastolic function of the left   ventricle and represents a sensitive indicator for many types of heart diseases.Objective: to evaluate the effects of gestational hypertension on the maternal myocardial function during  the third trimester by measuring the Tie index using transthoracic echocardiography.Method: This study was performed in Baghdad teaching hospital in the time period from November 2015  to August 2016. The study included a total of 150 women; 100 women had gestational hypertension, in the third trimester of a singleton pregnancy and with a mean age (29.83 ± 5.33 year), gestational hypertension   was identified as elevated systolic or diastolic blood pressure over 140/90 mmHg that emerges after the20th week of gestation with proteinuria level lower than 300 mg/dl. Another 50 normotensive pregnant   women with singleton pregnancy and mean age (28 ± 3.18 year) were used as controls. Left ventricular  mass index (LVMI) and relative wall thickness (RWT) were measured to find the type of hypertrophy in  gestational hypertension. Ejection fraction (EF) was measured with 2D directed M mode echocardiography,and isovolumic relaxation time (IVRT), isovolumic contraction rime (ICT) and ejection time (ET) were  measured for both groups using pulse wave Doppler echocardiography in order to calculate the myocardial  performance index which is also called “Tei index” and equals the sum of IVRT and IVCT divided by theET (Tei index = IVRT+IVCT/ET).Results: Left ventricular mass index and relative wall thickness were significantly higher in gestational hypertensive women, 41% of gestational hypertensive women had normal geometry and 59% had abnormal  geometry (34% eccentric hypertrophy, 19% concentric hypertrophy and 6% concentric remodeling). IVRT and IVCT were significantly higher in gestational hypertensive women with p value of 0.0001 and P =0.003. ET showed a non-significant lower values (p= 0.34) in gestational hypertensive women. Tei index     was significantly higher in Gestational hypertension (P=0.011).Conclusion: Women with gestational hypertension had altered myocardial function characterized by the             higher Tei index values associated with eccentric hypertrophy which can be explained by the fact that gestational hypertension poses higher afterload on the left ventricle instead the state of low peripheral resistance that is ysually expected during normotensive pregnancy.